Pengaruh Cairan Hasil Menyirih Terhadap Hambatan Pertumbuhan Bakteri Streptococcus Mutans (In Vitro) - Andriani, Tika, drg. Mahmud Kholifa, MDSc, drg. Suyadi (2015)
Dental caries is a common endemic disease of oral tissue with high severity. Streptococcus mutans was the main microorganism that cause dental caries, along with other 4 factors, host, agent, environment, and time. Other risk factor is behaviour and habit of the people, one of them was betel chewing. Betel chewing was the common habit of people who chew some betel leaves, uncaria, or lime paste, which usually mixed witb betel nut or tobacco. The purpose of this study was to understand the effect of betel chewing liquid toward Streptococcus mutans growth inhibition by reviewing inhibition zone using disk diffusion method. This was true experimental laboratory study with post test only control group design. Sampe were divided into 5 treatment groups which were treated with different liquids, betel chewing liquid on 5%, 10%, 20%, 40%, 80% concentration and negative control material. They were then replicated 4 times, and being incubated for 24 hours within 37°C temperature degree. Clear zone were measured using millimeter calliper. The result showed that betel chewing liquid has an effect on inhibition of bacterial growth Strectococcus mutans. In conclusion, 80% concentration of betel chewing liquid has the biggest inhibition against bacteria growth and the diameter of inhibition zone was bigger along with the increasing of betel chewing liquid concentration.